Effects of fabric-based unbalances on process-induced distortions of composite materials. (May 2015) - Brauner, Christian; Pereira, Guilherme Cybis; Herrmann, Axel S
In the present study, process-induced residual stresses of composite materials have been analysed on the mesolevel of a fabric unit cell. The given fabric was the satin-weave G0926, which is used for example in high-lift application of aerospace structures. In the study, a developed viscoelastic cure-dependent material model is applied to analyse the process-induced deformations of the fabric. In fact of the weave structure, this type of fabric tends to be out-of-plane displacement based on chemical and thermal shrinkage. This effect is studied experimentally and numerically, and the results are compared. The knowledge of the sensitivity of this fabric for out-of-plane displacement is an important factor to create real symmetric laminates. Disrespecting can be the source for large scattering warpage on the component level, and therefore, this awareness of the effect of textile structures on process-induced deformations is one key factor to develop robust processes.